Recent Progress in Polymer-Based Building Materials. (2nd December 2020) - Shen, Jingjing; Liang, Jianwei; Lin, Xinfeng; Lin, Hongjian; Yu, Jing; Yang, Zhaogang
Abstract : With the development of human society, the requirements for building materials are becoming higher. The development of polymer materials and their application in the field of architecture have greatly enhanced and broadened the functions of building materials. With the development of material science and technology, many functional materials have been developed. Polymer materials have many excellent properties compared with inorganic materials, and they can also be improved to enhance functional properties by blending or adding various additives (such as flame retardants, antistatic agents, and antioxidants). In this paper, polymer-based building materials are introduced with three classes according to the applications, that is, substrates, coatings, and binders, and their recent signs of progress in the preparations and applications are carefully demonstrated.